THE STUDY OF FEMINISM IN THE NOVEL NAYLA BY DJENAR MAESA AYU - Kusumaningrum, Ni Ketut Veri; Rasna, I Wayan; Artawan, Gde (Universitas Pendidikan Ganesha, 2019)
This research aims to determine (1) the narrative structure of novel Nayla by Djenar Maesa Ayu, (2) the role of women figure in the novel Nayla by Djenar Maesa Ayu, (3) the struggle of women figure in the novel Nayla by Djenar Maesa Ayu. This research uses feminism study with qualitative research. The data was collected by using library research. The library method was used at finding out the data in the novel Nayla by Djenar Maesa Ayu and in other literature which supports this research. The analyzed data are narrative structure, the role of women figure and the struggle of women figure in the novel Nayla by Djenar Maesa Ayu. The data were analyzed through the stage of reduction, presentation and data collection. The subject of this research is the novel Nayla by Djenar Maesa Ayu, the object of this research is the narrative structure, the role of women figure and the struggle of women figure in the novel Nayla by Djenar Maesa Ayu. The result of this research refers to (1) The Narrative structure in the novel Nayla by Djenar Maesa Ayu was include figure, characterization, plot and background. (2) The role of women figure in the novel Nayla by Djenar Maesa Ayu was found in the social domain, domestic and public. (3) The struggle of women figure in the novel Nayla by Djenar Maesa Ayu was manifested by struggling in maintaining in the status as women, the struggle in maintaining the gender. The form of feminism was described in the novel Nayla as never surrender, not dependent to the parents, and behaves deviate. Novel Nayla to present the relationship of gender that leads to a superior. Novel Nayla as the main character show business to make a women who has the dignity of which is equivalent to the men. Based on the results of analysis and advice for women in order to improve the quality of the field of education, domestic, and the public so that gender equality can be achieved.